Connection between a Column and its Foundation for Guadua Angustifolia Structures under Lateral Loads (2015)
In Colombia, as in other developing regions, social housing shortage related problems has led local authorities to propose low cost housing projects that allow its quickly and easy construction. Among the requirements of this type of construction are solicitations for vertical and lateral loads caused by wind or earthquake forces, as well as the sustainable use of natural resources Considering this, the use of Guadua angustifolia Kunth (Guadua a.) as a structural material has awaken a great interest, considering its renewability, high-speed growth, ecological benefits and because is easily obtainable all across the country. Due to the lack of additional information, structural joints in this type of materials, are usually pinned, assuming that there is no moment transmission between the different elements, however, some types of connections can partially restrict the rotation in the supports. Additionally, the degree of constrain that any support can provide to the column is a variable that has not been studied enough, despite being essential for modeling and structural design.In this work a connection between a column of Guadua a. and its foundation was studied. The influence of each component on the connection behavior under horizontal loads was assessed, testing seven different configurations. Monotonic and dynamic testing of connections as well as the characterization of the materials used in its construction were included in the experimental schedule. It was determined that the presence of mortar grouting together with the use of longitudinal bolts slightly increases the connection strength as drastically reduce its ductility. The use of transversal bolts is the best alternative to obtain a strong, stiff and ductile connection, especially when are combined with the use of hoops.